The Global Fingerprint of Modern Ice‐Mass Loss on 3‐D Crustal Motion - Sophie Coulson; Mila Lubeck; Jerry X. Mitrovica; Evelyn Powell; James L. Davis; Mark J. Hoggard (Geophysical Research Letters)
Abstract Crustal motion generated by rapid ice‐mass loss from Earth's glaciers and ice sheets has previously been considered in Global Navigational Satellite System (GNSS) analyses and numerical models across regions of ice retreat. However, the fingerprint of ice‐mass loss is not limited to glaciated areas, but is characterized by a global pattern of 3‐D crustal deformation. We compute “far‐field” vertical and horizontal deformation rates that occurred in response to early 21st century mass flux from the Greenland and Antarctic Ice Sheets, global glaciers and ice caps, and associated ocean loading. We demonstrate that mass changes in the Greenland Ice Sheet and high latitude glacier systems each generated average crustal motion of 0.1–0.4 mm/yr across much of the Northern Hemisphere, with significant year‐to‐year variability in magnitude and direction. Horizontal motions associated with ice‐mass loss exceed vertical rates in many far‐field areas, and both should be considered in future analysis of GNSS measurements.